2023
DOI: 10.1097/coc.0000000000001003
|View full text |Cite
|
Sign up to set email alerts
|

Unknown Causes of Death in Cancer Patients

Abstract: Objectives: Deaths from an unknown cause are difficult to adjudicate and oncologic studies of comparative effectiveness often demonstrate inconsistencies in incorporating these deaths and competing events (eg, heart disease and stroke) in their analyses. In this study, we identify cancer patients most at risk for death of an unknown cause. Methods: This retrospective, population-based study used cancer registry data from the Surveillance, Epidemiology, and End Results database (1992-2015). The absolute rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, these efforts are often adequate for a minimal number of cancers. Overall, it is well known that cancer therapy can lead to many other problems, described as possible side effects and affecting distant organs than the one involved by the cancer itself [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these efforts are often adequate for a minimal number of cancers. Overall, it is well known that cancer therapy can lead to many other problems, described as possible side effects and affecting distant organs than the one involved by the cancer itself [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these efforts are often adequate for a minimal number of cancers. Overall, it is well known that cancer therapy can lead to many other problems, described as possible side effects and affecting distant organs than the one involved by the cancer itself [3]. Stoltzfus et al described a study amongst 7.5 million cancer patients and identified that those who were diagnosed <40 years of age were more likely to die of heart disease when diagnosed with breast cancer or lymphoma; patients diagnosed >40 years of age were more likely to die from heart disease when diagnosed with prostate, lung, and colorectal cancers [4].…”
Section: Introductionmentioning
confidence: 99%